Development and feasibility of a driving training program for Autistic student drivers. - Priscilla Vindin; Reinie Cordier; Nathan J Wilson; Lauren Parsons; Hoe Lee (PLoS ONE, 2025)
Driving licencing rates remain lower for autistic individuals capable of driving a motor vehicle, which can limit achieving independence in community mobility. However, there is limited autism-specific guidance in current driver training. The development and evaluation of the feasibility of an autism-specific Driving Training Program (DTP) intervention was conducted to improve the likelihood that autistic student drivers will safely and successfully learn to drive a motor vehicle and gain a driver's licence. The DTP intervention was developed using a modified stepped approach for developing complex skills-based interventions. The Goals for Driving Education framework for explaining driving training behaviour modification formed the foundation of the intervention. A small-scale study was conducted using a single group pre-post-test design (n = 5), followed by semi-structured interviews and a survey (n = 12) to evaluate the feasibility of intervention components and participant acceptability. The driving performance of the autistic student drivers significantly improved, demonstrating the feasibility of the DTP intervention for training autistic student drivers to learn to drive. Participants also found the intervention acceptable, with program component refinement suggested. The DTP intervention is feasible for a larger randomised controlled trial after modifying highlighted program components.